(untitled) (مجلة الواحات للبحوث والدراسات, 2026)
Guidance programs have received significant attention from researchers and therapists. It has thus become a prominent feature of psychological services programs. Planning and implementing it has become an essential skill for counselors or psychological specialists, given its significant impact in finding solutions to many psychological, social, and academic problems. Based on this, we will attempt, through this intervention, to shed light on guidance programs in terms of their concept, characteristics, and features. We will then address the theoretical foundations for constructing guidance programs and the strategies used in them, adopting the descriptive approach because it is appropriate for such studies.